Assistance In Increasing Productivity of the Kosagrha Lestari Farming Group Based On Ecopreneurship - Ayun Maduwinarti; I.G.N. Andhika Mahendra; Putri Chandra Ayu Pitaloka; Aflyah Salsabila (International Conference of Innovation and Community Engagement, 2025)
Surabaya is one of the capitals of East Java Province, Indonesia, and it also has many tourist attractions that are frequently visited by local and international tourists, including Tunjungan Street, the Old Town, and many more. Although Surabaya is known as the City of Heroes, on the other hand, in the eastern region, specifically in South Medayu, Rungkut District, there is a diverse and interesting educational urban farming tourism. The location of this village is very strategic, serving as a center for the sale and education of organic plants, as well as livestock and fisheries, with various types of organic plants, including water spinach, mustard greens, lettuce, spinach, and other freshwater fish. Our partner is an MSME engaged in the field of urban farming. The current condition of the partner is the limitation of animal feed production tools to create a zero-waste environment. The increasing number of residents from Dusun Medayu joining has created a positive platform for its members and also provides economic benefits; therefore, the competition in that business is becoming more intense. Therefore, the ability and knowledge of digital-based marketing are essential for partners to possess. This Community Service Program will support short-term activities such as business coaching and digital marketing training. In the medium term, as a continuation after the 2024 Community Service Program, the Implementation Team will conduct a reassessment of local businesses that have the potential to support the development of current partner enterprises. This mapping is expected to serve as a reference for the sustainability of the partners’ independent programs.